Military training and patriotic upbringing as a determinant of effective management of youth work in universities in the context of a unilateral military action - P. V. Klimenko; O. V. Shpyrnya (Вестник Майкопского государственного технологического университета, 2025)
Abstract. In the context of a unilateral military operation, military training and patriotic upbringing of university youth becomes relevant.The goal of the research has been formulated due to the presence of a certain gap between the level of , military training and patriotic upbringing of university yourh and modern challenges facing our country in the context of a unilateral military operation. The goal of the research is to identify the main problems of, military training and patriotic upbringing, and to propose the main ways of effectively organizing work with young people in universities.The research results: it has been determined that in the last 20 years there has been a process of deformation of traditional values among young people, which entailed alienation from the state, its traditions, culture, language, and in some cases, opposition to state interests. Taking into account the unilateral military operation, it is military training and patriotic upbringing that becomes the main determinant of the effective organization of work with young people in universities.Key findings: military training and patriotic upbringing as a determinant of effective organization of work with young people in universities in the context of a special military operation is the most important element of the pedagogical activity of the faculty. Organization of military training and patriotic upbringing in universities should imply a change in approaches to educational and social work with young people, paying more attention in the curricula to issues of history, culture, morality, volunteerism, service to the state and society, as well as physical education of student.